PERAN BIDAN DALAM MEMBERIKAN ASUHAN KESEHATAN REPRODUKSI REMAJA DI PMB WILAYAH NAGOYA KOTA BATAM - Purba, Netty Herawaty; Husnah, Ridni; Nuraina, Siti (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Reproductive health is a state of complete physical, mental and social health, not solely free from disease or disability related to the reproductive system, functions and processes. The purpose of this study was to determine the role of midwives in providing adolescent reproductive health care at PMB Nagoya Region, Batam City. The research method used in this study is a qualitative descriptive research design. The selection of informants was determined using a purposive sampling technique. By conducting interviews with 5 midwives and 5 adolescents. The results of this study are the role of midwives as communicators, namely providing information related to reproductive health, providing information related to balanced nutrition and providing information about menstrual disorders in adolescents. The midwife's role as a motivator is by advising good things related to the disorders they experience such as maintaining cleanliness, avoiding stress, getting enough rest for cases of menstrual disorders that often appear in adolescents. The midwife's role as a facilitator is to provide a place for adolescents regarding adolescent reproductive health, besides that midwives also provide HB checks and provide FE tablets to adolescents who need them. The role of midwives as counselors is to provide counseling to adolescents regarding reproductive health, where midwives always listen to adolescent complaints well and provide information to adolescents according to complaints experienced. The conclusion from this study is that midwives have provided care in accordance with the midwife's role in providing reproductive health care to adolescents